2016
DOI: 10.1364/oe.24.030328
|View full text |Cite
|
Sign up to set email alerts
|

Single-shot terahertz time-domain spectroscopy in pulsed high magnetic fields

Abstract: We have developed a single-shot terahertz time-domain spectrometer to perform optical-pump/terahertz-probe experiments in pulsed, high magnetic fields up to 30 T. The single-shot detection scheme for measuring a terahertz waveform incorporates a reflective echelon to create time-delayed beamlets across the intensity profile of the optical gate beam before it spatially and temporally overlaps with the terahertz radiation in a ZnTe detection crystal. After imaging the gate beam onto a camera, we can retrieve the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 31 publications
0
21
0
2
Order By: Relevance
“…We decided for transmissive 26,30 instead of the more commonly used reflective echelons. 28,[31][32][33] The latter are typically CNC (computerized numerical control) machined single pieces of metal. However, we found that it was impossible to produce optically flat steps of the required size in that way.…”
Section: A 2d-raman-thz Implementationmentioning
confidence: 99%
“…We decided for transmissive 26,30 instead of the more commonly used reflective echelons. 28,[31][32][33] The latter are typically CNC (computerized numerical control) machined single pieces of metal. However, we found that it was impossible to produce optically flat steps of the required size in that way.…”
Section: A 2d-raman-thz Implementationmentioning
confidence: 99%
“…In addition to using a standard delay-stage-based stepscan THz setup combined with a 10-T superconducting magnet [45][46][47][48][49][50][51][52], we used a unique single-shot THz setup to perform measurements in pulsed magnetic fields up to 30 T [40]. Pulsed magnets typically generate higher magnetic fields with a smaller magnet and cryostat size than DC magnets, but the challenge is that the peak magnetic field only lasts for a short time (approximately 400 µs in our case [38]), so that the time for a delay stage to step through the THz waveform is insufficient.…”
Section: Single-shot Thz Spectroscopy In Pulsed High Magnetic Fieldsmentioning
confidence: 99%
“…1) is well established [10,13,[34][35][36], although some controversy remains as to whether surface states in the SM region are topologically nontrivial [37]. We performed measurements using a single-shot THz time-domain polarimetry setup combined with a 30-T pulsed magnet system [38][39][40]. The wide tunability of the band structure of Bi 1−x Sb x with x makes this material system suitable for identifying and distinguishing the uniquely different magneto-optical responses of samples in the topologically trivial and nontrivial phases.…”
Section: Introductionmentioning
confidence: 99%
“…Сейчас для преобразования одиночного ультракороткого импульса в серию эквидистантных во времени в пространстве копий используются конструкции типа эшелона Майкельсона [23,24]. Одной из систем, обеспечивающих аналогичное повторение и используемых для решения задач поиска и изучения свойств экзопланет, сегодня является стремительно развивающаяся техника, имеющая в своей основе интерферометр Фабри−Перо (ИФП).…”
Section: фильтр на основе зеркала (линзы) френеляunclassified